The Introduction and the Application of Technological Innovations as Administrative Efficiency Factor in Education - D., Belias; Velissariou E.; Kyriakou D; Koustelios a.; Sdrolias L.; Varsanis K. (European Journal of Social Science Education and Research, 2017)
Innovation is a rapidly developed issue, keeping all the aforementioned alerted. Considering this picture, the key issue of this thesis is to clarify the concept innovation as administrative efficiency factor in relation with education using the relevant literature. The existing literature indicates that educational structure and practices are in the center of great reforms. These reforms associated with New Public Management. NPM is a process that involves interaction between managers and markets. It is a set of cost-cutting and management concepts from the private sector including downsizing, entrepreneurialism, enterprise operations, quality management, customer service etc. According to that concept, school managers are trying to create a smaller, more responsive, more entrepreneurial and more effective public sector. Technological innovation has a key role on this and surely it can be the cornerstone of every change which may occur on this field of public administration.